A Novel Device for the Dilatometric Study - Zeriouh, A.; Belkbir, L. (Asian Journal of Chemistry, 2010)
In this work we are interested to develop an adequate dilatometric method which allows to measure quantitatively the dimensional changes occurring during thermal treatment of solids and most precisely to determine their specific characteristics. The research allowed us to realize an experimental dilatometer able to follow the evolution of dimensional changes of solids whatever their physical and chemical nature is. With the help of this new device, the experimental results show that the temperature phase transformations and the thermal stability of the studied samples become easily accessible to the operator of these materials.